2022
DOI: 10.3390/molecules27031084
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Flowers and Leaf Extracts Obtained from Turnera subulata and Their Immunomodulatory Effect on LPS-Activated RAW 264.7 Macrophages

Abstract: The anti-inflammatory properties of Turnera subulata have been evaluated as an alternative drug approach to treating several inflammatory processes. Accordingly, in this study, aqueous and hydroalcoholic extracts of T. subulata flowers and leaves were analyzed regarding their phytocomposition by ultrafast liquid chromatography coupled to mass spectrometry, and their anti-inflammatory properties were assessed by an in vitro inflammation model, using LPS-stimulated RAW-264.7 macrophages. The phytochemical profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 66 publications
1
20
0
1
Order By: Relevance
“…Cytotoxicity Tests. With the aim of investigating the toxicity of the Sn−Ni−Zn alloys, cytotoxicity tests (cell viability) 43 were carried out using the Pb-10 wt % Sn and Sn-20 wt % Pb alloys as a standard for comparison. Furthermore, the effect of Zn content and microstructural scale on the cytotoxicity behavior of each DS casting has been evaluated.…”
Section: Solidification Thermal Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity Tests. With the aim of investigating the toxicity of the Sn−Ni−Zn alloys, cytotoxicity tests (cell viability) 43 were carried out using the Pb-10 wt % Sn and Sn-20 wt % Pb alloys as a standard for comparison. Furthermore, the effect of Zn content and microstructural scale on the cytotoxicity behavior of each DS casting has been evaluated.…”
Section: Solidification Thermal Variablesmentioning
confidence: 99%
“…Alamar Blue Reduction Cytotoxicity Assay. In order to confirm the cytotoxic effect of the Sn−Cu−Zn and Sn−Ni− Zn alloys against the 3T3 cell line, the Alamar Blue colorimetric method 43 was used, which contains a redox indicator that, in the presence of metabolically active cells, changes from the oxidized form (blue and non-fluorescent) to the reduced form (pink and fluorescent). For this, cells (3 × 10 4 cells/well) were cultured in 96-well plates for 1 h for adhesion.…”
Section: Solidification Thermal Variablesmentioning
confidence: 99%
“…The ability of Turnera subulata to regulate the central nervous system neurotransmitter, gamma-aminobutyric acid (GABA), is the primary cause of its antianxiety effects [59,60]. Additionally, the antioxidants found in the plant play an effective role in eliminating free radicals and reducing oxidative stress, protecting against cellular damage [61,62]. Therefore, due to the antioxidant quality of this plant, the use of plant extracts significantly contributes to the prevention of chronic diseases related to oxidative stress and overall health promotion, as pointed out by Annadurei et al [63].…”
Section: Turnera Subulatamentioning
confidence: 99%
“…Among the previously mentioned pharmacological properties of Turnera subulata, its anti-inflammatory property stands out, showing potential for use in the treatment of neurodegenerative diseases. A study conducted by Luz et al [62] investigated the immunomodulatory effect of the floral and leaf extracts of this plant in an in vitro model of acute inflammation using macrophages. The results obtained revealed that the bioactive molecules of Turnera subulata have a promising advantage regarding side effects.…”
Section: Turnera Subulatamentioning
confidence: 99%
“…The cells were treated with 1 and JR-9 for 48 h, camptothecin (positive control), or vehicle control (0.1% DMSO) before being combined with 20µL of MTT solution (final concentration of 0.25mg/mL). After 4 h of incubation, the supernatant was removed, the formazan crystals were dissolved in 100µL DMSO, and absorbance at 570 nm was measured with a Synergy Mx microplate reader (Bio-Tek, USA) [35]. The average of quadruplicate determinations with the mean standard error was used to illustrate the findings (SD).…”
Section: Mtt Assaymentioning
confidence: 99%